Uterine didelphys with concomitant renal anomalies in both mother and fetus - Maren Boehnke; Michael V. Zaretsky; Danielle E. Soranno; Kimberly A. Dannull; Bethany D. Tucker; Ahmed I. Marwan (Elsevier, 2016)
Uterine didelphys results from impaired fusion of the paired Müllerian ducts. The incidence of uterine anomalies is believed to be 0.5-2.0% of reproductive-age women, with didelphic uterus accounting for approximately 10%. Uterine didelphys is associated with renal agenesis in approximately 25% of cases. We present a case of didelphys uterus with a left solitary kidney in a mother whose female fetus also demonstrated uterine didelphys with right multicystic dysplastic kidney. This report highlights the significant contribution and complimentary role of fetal MRI in identifying fetal anomalies.